O Procedimento de pré-mediação institucional do poder judiciário de Pernambuco - Melo, Flávio Porpino Cabral de (2011)
This research has the object of study of the experience of pre - mediation sessions imposed by the judiciary of Pernambuco in order to investigate , describe and analyze the partition structure of the interlocutors, by recording the event and subsequent transcription and formatting transcription for analysis of the material by the Critical Discourse Analysis approach , in particular , analysis of speech in institutional interaction. As a counterpoint , there is what effectively in practice the pre - mediation match prescriptive framework that the Judiciary of Pernambuco was imposed to institutionalize the Auxiliary System Conflict Resolution , formalized through Central Conciliation , Mediation and Arbitration ( Resolution No. 222/2007 of 04/07/2007 , articles 73 and 74 of the Code of Judicial Organization of the State of Pernambuco - State Complementary Law No. 100 of 21/11/2007 ) . This factual context , crystallize very important social issues , particularly on the Right , since studying the Judiciary of Pernambuco public policy , recently implemented and not subjected to this kind of approach . But also contributes to the nucleation and consolidation of research activities in view of the Scythian Discourse Analysis ( CDA) in Law .